BIOL-07. MIR-212 FUNCTIONS AS A TUMOR SUPPRESSOR GENE IN GROUP 3 MEDULLOBLASTOMA VIA TARGETING NUCLEAR FACTOR I/B (NFIB). (1st June 2021) - Perumal, Naveenkumar; Kanchan, Ranjana; Doss, David; Atri, Pranita; Venkata, Ramakanth Chirravuri; Thapa, Ishwor; Nasser, Mohd; Batra, Surinder; Mahapatra, Sidharth
Abstract: Medulloblastoma (MB), the most frequent malignant pediatric brain tumor is subdivided into four primary subgroups, i.e. wingless-type (WNT), sonic hedgehog (SHH), group 3, and group 4. Haploinsufficiency of chromosome 17p13.3 and c-myc amplification distinguish high-risk group 3 tumors, which are associated with rapid metastasis, recurrence and early mortality. We sought to identify the role of miR-212, which resides on chromosome 17p13.3, in the pathophysiology of group 3 MB. RNA expression analyses revealed dramatically reduced levels of miR-212 in group 3 tumors and cell lines mainly through epigenetic silencing via histone modifications (deacetylation). Restoring in vitro miR-212 expression reduced tumor cell proliferation, colony formation, wound healing, migration and invasion with decreased p-AKT and p-ERK levels in group 3 MB cell lines. Interestingly, a shift in differential c-myc phosphorylation (from serine-62 to threonine-58) was also discovered with miR-212 expression, resulting in reduced total c-myc levels, concurrent with elevated cellular apoptosis. In turn, pro-apoptotic binding partners of c-myc, i.e. Bin-1 and P19ARF, were upregulated in these cells. These findings were recapitulated in stable inducible miR-212 expressing tumor cells. Using a combination of transcriptomic data and a dual luciferase assay, we isolated an important oncogenic target of miR-212, i.e, NFIB, a nuclear transcription factor implicated in metastasis and recurrence. Increased expression of NFIB was confirmed in group 3 tumors, with poor survival shown in high NFIB-expressing patients. As prior, transient NFIB silencing in vitro reduced not only tumor cell proliferation, colony formation, wound healing, migration and invasion, but also medullosphere formation along with decreased expression of stem cell markers (Nanog, Oct4, Sox2, CD133), confirming its role in tumor recurrence possibly via augmenting tumor stemness. Taken together, these results substantiate the tumor suppressive role of miR-212 in group 3 MB and provide a potential new oncogenic target implicated in tumor recurrence, NFIB.